A combined critical distance and highly-stressed-volume model to evaluate the statistical size effect of the stress concentrator on low cycle fatigue of TA19 plate. (February 2017) - Wang, Rongqiao; Li, Da; Hu, Dianyin; Meng, Fanchao; Liu, Hui; Ma, Qihang
Highlights: Design and conduct systematic experiments of TA19 plates with a central circular hole cut from an actual compressor disc under LCF loading. Demonstrate the statistical size effect based on the test results of plate specimens with different scales. Establish a combined critical distance and highly-stressed-volume model to evaluate the statistical size effect in the analysis of notch fatigue. Abstract: Titanium alloy has been widely used for compressor discs in aero-engines due to its high specific strength. As a common geometry feature in compressor discs, bolt hole with stress concentration can cause compressor discs to fail under low cycle fatigue (LCF). In this study, the statistical size effect of such stress concentrators was investigated by LCF experimentations and theoretical predictions for titanium alloy plate specimens with a central circular hole (CHP). Four different scales of test sections without the influence of geometrical size were specially designed and experimental tests were conducted under LCF loading at 180 °C. The strain-controlled LCF tests of smooth specimen were also carried out at the same temperature. It is found that the predicted LCF lifetime from the theory of critical distance (TCD) correlates well with experimental results for the 100%-scale CHP specimens. However, it fails to accurately predict the dependence of LCF lifetime on the statistical size effect for CHP specimens at the other scales i.e., 40%-scale, 60%-scale, and 80%-scale. Furthermore, a novel methodology combining the TCD and highly-stressed-volume models is proposed to evaluate the statistical size effect, which exhibits much improved accuracy than the TCD method alone. The new model not only inherits the versatility of the TCD method but providing an essential assessment of the statistical size effect.